Analysis of E-Service Quality Attributes in Delivery Service Application Using the Kano Model - Kumala, Khofifah Ela; Haunan Damar; Imam Nuryanto; Handy Nur Cahya (International Journal of Economics, Management and Accounting, 2025)
GoSend as an instant delivery service from Gojek plays an important role in meeting the demand for fast and reliable delivery. However, there are still challenges in terms of service quality, customer satisfaction, and competitiveness in the digital logistics industry. This study analyzes GoSend's electronic service quality attributes using the Kano Model to identify the factors that most influence customer satisfaction. The quantitative method is applied through a survey of 206 GoSend users in Semarang, with the integration of E-Servqual indicators and Kano Model attributes. The results of the study show that most service attributes fall into the "Indifferent" category, meaning they do not have a significant effect on customer satisfaction. However, attributes such as transaction data security and item conditions fall into the "One-Dimensional" category, so improvements in these aspects can increase customer satisfaction. The analysis of the Extent of Satisfaction (EOS) and Extent of Dissatisfaction (EOD) shows that responsiveness to complaints and service personalization still need to be improved. Based on these findings, strategic recommendations that can be given are increasing customer service responsiveness, optimizing compensation policies, and strengthening security systems to increase customer trust. The integration of the Kano Model with E-Servqual provides a comprehensive evaluation of the quality of digital logistics services while also being a guide for GoSend in increasing customer satisfaction and loyalty amidst increasingly fierce competition.